Kearifan Lokal dan UMKM Kreatif: Kunci Revitalisasi Ekonomi Inklusif di Era Digital - Misbahul Arifin; Durrotul Masruroh; Chusnul Muali (An Nafi': Multidisciplinary Science, 2025)
This research delves into the application of the Community-Based Development Model (CBDM) to empower MSMEs rooted in local wisdom within Probolinggo Regency, contributing to participatory and sustainable community economic development. The core focus is to understand how community engagement, leveraging local potential, and digitalization drive collective economic independence. Employing a qualitative approach with a case study method, data was gathered via in-depth interviews, observation, documentation, and thematic analysis. Findings highlight five key stages in CBDM implementation: identifying local potential, community involvement, MSME capacity building, executing culture-based programs, and evaluating economic independence. This implementation successfully boosted MSME turnover by 57%, spurred citizen participation in village economic forums, and independently strengthened digital marketing capabilities. These results demonstrate that development rooted in local participation and culture not only enhances the economy but also reinforces community social cohesion, offering a replicable development model for similar regions.